2017
DOI: 10.1155/2017/4049061
|View full text |Cite
|
Sign up to set email alerts
|

Dilute Alkali and Hydrogen Peroxide Treatment of Microwave Liquefied Rape Straw Residue for the Extraction of Cellulose Nanocrystals

Abstract: Microwave-assisted liquefaction of rape straw in methanol was conducted to collect the liquefied residues for the extraction of cellulose nanocrystals (CNCs). The liquefied residue with content of 23.44% from 180°C/7.5 min was used to fibrillate CNCs with dilute alkali (2% NaOH) and hydrogen peroxide (5% H2O2) treatments, followed by ultrasonication for 15 min. The FT-IR spectra and SEM images revealed that the liquefied residue from 180°C/7.5 min exhibited a relatively homogeneous texture and a huge surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“… 5 Furthermore, sulfuric acid hydrolysis used to produce nanocellulose could introduce negatively charged sulfate ester. 55 This could contribute to attracting positive charged cationics. By increasing the pH from 3 to 11, the MB adsorption capacity of PUB 1 increased from 0.48 to 2.34 mg/g with 98.61% MB removal efficiency and that of PUα 1 increased from 0.50 to 2.32 mg/g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Furthermore, sulfuric acid hydrolysis used to produce nanocellulose could introduce negatively charged sulfate ester. 55 This could contribute to attracting positive charged cationics. By increasing the pH from 3 to 11, the MB adsorption capacity of PUB 1 increased from 0.48 to 2.34 mg/g with 98.61% MB removal efficiency and that of PUα 1 increased from 0.50 to 2.32 mg/g.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was partially attributed to the hydrogen bonding formed between MB and PUN 1 that has a large number of −OH groups . Furthermore, sulfuric acid hydrolysis used to produce nanocellulose could introduce negatively charged sulfate ester . This could contribute to attracting positive charged cationics.…”
Section: Resultsmentioning
confidence: 99%
“…Further research found that the microwaveliquefied bamboo residues still retained the cell wall structure and tracing cellulose, and pure white cellulose fibers could be extracted from the residues with a mild bleaching process. Further treatment of the cellulose yielded nanofibrillated cellulosic fibers with lengths greater than 550 nm ( Figure 3) [50,89,90].…”
Section: Characterization and Utilization Of Liquefied Residuesmentioning
confidence: 99%
“…The raw material source of CNPs is abundant and can be made from wood, herbaceous plants, tunicates, algae, crab shells, bacteria, etc. [ 6 , 7 , 8 , 9 ]. The preparation methods of CNPs mainly include mechanical diminution (grinder, ultrasonic treatment, high-pressure homogenizer, and microfluidization), chemical diminution (sulfuric acid hydrolysis and hydrochloric acid hydrolysis), bio-enzyme methods, and combinations thereof [ 6 ].…”
Section: Introductionmentioning
confidence: 99%